The Role of Compensation as a Mediation on the Performance of Health Workers Influenced by Human Resources: Issue in the World of Medical Services - Asluchul Alif; Djoko Soelistya; Eva Decembrianita (Budapest International Research and Critics University, 2022)
Hospitals as one of the service industries face the challenges of globalization that can hinder development as well as become opportunities for advancement. Hospitals are required to “be able to absorb the aspirations that develop in society and also have to make adjustments in services to improve hospital performance, because the intense competition between hospitals demands that hospitals as service providers are required to always pamper consumers by providing the best service, so that performance medical personnel must be really good at supporting the quality of service, with adequate human resources.” Therefore, “the purpose of this study is to analyze the importance of service quality and human resources (HR) in influencing the performance of medical personnel through compensation provided by the organization. The following research uses a quantitative approach that has a population of all health workers and the sample is 68 respondents, which is called a saturated sample. And for the analysis model using the analysis program SmartPLS 3.0.”This study resulted that (1) “the quality of human resources directly affect the performance of health workers; (2) the quality of human resources has a direct effect on compensation; (3) compensation has a direct effect on the performance of health workers, while the results of the indirect effect test show that (4) the quality of human resources can directly affect the performance of health workers even without going through compensation as a mediation, therefore there needs to be attention in improving the quality of human resources and compensation that has been given by the organization to health workers so that health workers will further improve their performance.”